The Role of Madrasah Ibtidaiyah in Character Building and Student Independence: An In-depth Study of Basic Education Based on Religious Values - Napi'ah, Adeliya Siti; Ayuningsih, Resti Fatma (Sekolah Tinggi Ilmu Tarbiyah Bustanul 'Ulum Lampung Tengah, 2025)
This study investigates the role of Madrasah Ibtidaiyah in shaping students' character and independence through an in-depth exploration of primary education grounded in religious values at MI AL-ASY'ARI Keras Diwek Jombang. The background highlights the importance of integrating religious values into basic education to foster holistic student development. The research aims to examine how MI AL-ASY'ARI promotes character formation and student independence within the context of religious values. The methodology involves qualitative research methods including interviews, observations, and document analysis to gather comprehensive data. Findings suggest that MI AL-ASY'ARI effectively cultivates students' character strengths and independence through its integrated approach to religious education. The implications underscore the significance of religious-based education in nurturing well-rounded individuals capable of contributing positively to society. This study contributes to the discourse on educational practices that integrate religious values in fostering character development and student autonomy at the primary school level.